Remote Temperature Sensor Implementation Using Amplitude Shift Keying - F.A., Aigbodioh; C.N., Muoghalu (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
The project “Remote Temperature Sensor” implemented using the Amplitude Shift Keying (ASK) was designed and constructed to ensure that the temperature of an environment or object (where the Sensor/Transmitter unit is located), can be monitored from a completely different remote location (where the Receiver/Display unit is located) In the sensor/transmitter unit, an IC temperature sensor (LM 335) senses the temperature of the environment or object to be measured, from which pulses are generated. The pulse switches “ON” and OFF a Colpitt oscillator and the period in which the oscillator is switched “OFF” is proportional to the temperature being sensed. The receiver unit which comprises mainly the TDA 7000 single IC and a “slack handful” of capacitors picks up the Radio Frequency (RF) signal generated by the Colpitt oscillator. This processes the signal to give seven-segment display read-out values, which corresponds to the temperature being sensed by the Sensor/Transmitter unit. The system is able to monitor the temperature of a remote location up two meters away. About 100% accuracy was achieved for temperature ranging from 30 to 590C and an average of about +2.50C accuracy was achieved for temperatures above 590C.